2018
DOI: 10.1101/320119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potassium channel KCNJ13 is essential for smooth muscle cytoskeletal organization during mouse tracheal tubulogenesis

Abstract: Tubulogenesis is essential for the formation and function of internal organs. One such 49 organ is the trachea, which allows gas exchange between the external environment and 50 the lungs. However, the cellular and molecular mechanisms underlying tracheal tube 51 development remain poorly understood. Here, we show that the potassium channel 52 KCNJ13 is a critical modulator of tracheal tubulogenesis. We identify Kcnj13 in an 53 ethylnitrosourea forward genetic screen for regulators of mouse respiratory organ 5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…4). Mutations are known to cause defects in tracheal development in mice 63 and two rare diseases in humans leading to visual impairment [64][65][66][67][68][69][70] . During colour pattern formation in D. rerio, Kcnj13 function is autonomously required in melanophores 35 , and in ex vivo studies it was shown that the channel is involved in the contact-dependent depolarisation of melanophores upon interactions with xanthophores leading to a repulsion between these cells 39 .…”
Section: Resultsmentioning
confidence: 99%
“…4). Mutations are known to cause defects in tracheal development in mice 63 and two rare diseases in humans leading to visual impairment [64][65][66][67][68][69][70] . During colour pattern formation in D. rerio, Kcnj13 function is autonomously required in melanophores 35 , and in ex vivo studies it was shown that the channel is involved in the contact-dependent depolarisation of melanophores upon interactions with xanthophores leading to a repulsion between these cells 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Only recently have potential genetic mediators of smooth muscle alignment been identified in vivo. For example, mouse mutants for Wnt5a, its receptor Ror2, and the ion channels Kcnj13 and Tmem16a show misaligned smooth muscle in the mouse trachea and esophagus (Kishimoto et al, 2018;Rock et al, 2008;Yin et al, 2018), and mutations in the planar cell polarity (PCP) gene Dlgh1 cause a misalignment of muscle in the mouse ureter (Mahoney et al, 2006). It is, however, currently unclear whether these genes modulate tissue mechanics to organize muscle or whether their expression and cellular organization are downstream of mechanical cues, as demonstrated for PCP components within the mammalian skin (Aw et al, 2016).…”
Section: A New Paradigm For Understanding the Development Of Muscle Amentioning
confidence: 99%
“…The crucial functions of these genes are validated by Tbx4, 5 double mutants exhibiting the phenotypes of tracheal stenosis 10 . We previously reported that synchronized polarization of mesodermal cells and temporal initiation of cartilage development regulate tracheal tube morphogenesis by coordinating the length and diameter of the mouse trachea, respectively 13,14 . However, the mechanism underlying the initial induction of tracheal mesoderm is still unclear.…”
mentioning
confidence: 99%